Average geodesic distance on stretched Sierpiński gasket. (September 2021) - Li, Yuanyuan; Fan, jiaqi; Xi, lifeng
Highlights: The average distance on stretched Sierspinski gasket is calculated. The integral of geodesic distances in terms of a local-self-similar measure is established. The finite patterns of integrals are used. Abstract: The stretched Sierpiński gasket is a local self-similar set, but not strictly self-similar. By the local self-similarity of scale and measure, we calculate its average geodesic distance within the gasket by the method of finite pattern.